Dimethyl sulfide in the Amazon rain forest. Issue 1 (8th January 2015) - Jardine, K.; Yañez‐Serrano, A. M.; Williams, J.; Kunert, N.; Jardine, A.; Taylor, T.; Abrell, L.; Artaxo, P.; Guenther, A.; Hewitt, C. N.; House, E.; Florentino, A. P.; et al.
Abstract Surface‐to‐atmosphere emissions of dimethyl sulfide (DMS) may impact global climate through the formation of gaseous sulfuric acid, which can yield secondary sulfate aerosols and contribute to new particle formation. While oceans are generally considered the dominant sources of DMS, a shortage of ecosystem observations prevents an accurate analysis of terrestrial DMS sources. Using mass spectrometry, we quantified ambient DMS mixing ratios within and above a primary rainforest ecosystem in the central Amazon Basin in real‐time (2010–2011) and at high vertical resolution (2013–2014). Elevated but highly variable DMS mixing ratios were observed within the canopy, showing clear evidence of a net ecosystem source to the atmosphere during both day and night in both the dry and wet seasons. Periods of high DMS mixing ratios lasting up to 8 h (up to 160 parts per trillion (ppt)) often occurred within the canopy and near the surface during many evenings and nights. Daytime gradients showed mixing ratios (up to 80 ppt) peaking near the top of the canopy as well as near the ground following a rain event. The spatial and temporal distribution of DMS suggests that ambient levels and their potential climatic impacts are dominated by local soil and plant emissions. A soil source was confirmed by measurements of DMS emission fluxes from Amazon soils as a function of temperature and soil moisture. Furthermore, light‐ and temperature‐dependent DMS emissions were measured from seven tropical tree species. Our study has important implications for understanding terrestrial DMS sources and their role in coupled land‐atmosphere climate feedbacks.